2020
DOI: 10.1115/1.4048167
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Journal Bearing Thermal Effects on Rotordynamic Response

Abstract: Traditional analysis of journal bearings assumed a constant viscosity which simplified the solutions for static and dynamic characteristics and responses. Today's high-performance machinery requires more accurate models wherein temperature and viscosity distributions in the film must be calculated. Thermal effects in journal bearings have a strong influence on both static and dynamic properties, and consequently play a critical role in determining rotor-bearing system performance. This paper presents an extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 136 publications
0
7
0
Order By: Relevance
“…Furthermore, Jin et al [15] investigated the pivot stiffness effect on the vibration amplitude of TPJBs and showed that pivot stiffness leads to reduce the resonance and working amplitude of the system. Finally, Shin et al [16] published a review paper on thermal modeling methods for journal-bearing systems. They did not mention any previous works which simulated the effect of temperature-induced variations of the oil film viscosity on the dynamic behavior of a rotor-worn TPJB.…”
Section: Of 26mentioning
confidence: 99%
“…Furthermore, Jin et al [15] investigated the pivot stiffness effect on the vibration amplitude of TPJBs and showed that pivot stiffness leads to reduce the resonance and working amplitude of the system. Finally, Shin et al [16] published a review paper on thermal modeling methods for journal-bearing systems. They did not mention any previous works which simulated the effect of temperature-induced variations of the oil film viscosity on the dynamic behavior of a rotor-worn TPJB.…”
Section: Of 26mentioning
confidence: 99%
“…Some twenty years later, Brown et al [8] found that the rotating unbalance could induce chaotic vibration. Other nonlinear phenomena have connections with thermal effects [9] and friction or contact forces in self-equalising bearings [3]. Non-uniform shear stress in the oil film can heat the journal surface due to hydrodynamic friction.…”
Section: Briefly On Nonlinear Vibrations Induced By Journal Bearingsmentioning
confidence: 99%
“…If only a small part of the surface is heated repeatedly, a shaft bends, changing the unbalance distribution. This thermal instability is called the Morton effect [9]. Various bearing designs can suppress mentioned instabilities or undesirable rotor behaviour and effects.…”
Section: Briefly On Nonlinear Vibrations Induced By Journal Bearingsmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) has emerged as a significant approach for investigating the performance of journal bearings by directly solving flow equations without employing additional simplifications. For fixed journal bearings, Shin et al 14 conducted an extensive survey ranging from conventional Reynolds equation models to more advanced CFD models. For porous-type journal bearings, Balasoiu et al 15 conducted a 3D isothermal CFD analysis of a cylindrical porous journal bearing with a self-circulating lubricating system.…”
Section: Introductionmentioning
confidence: 99%